Historical evolution of the rural school in Cuba in the XIX-XX centuries (2016)
The history and evolution of the rural school in Cuba in the nineteenth and twentieth centuries is presented as a case study. The main methods of this research work are document review and key informant interviews. The results include and present a periodization ‘map’, consisting of three stages from 1816 until 1999. The study aims to add to the efforts already undertaken in the country in order to establish the Model of Primary School taking into consideration the peculiarities that rural areas contribute. The article does not attempt to provide complete answers but seeks instead to start an academic dialogue towards an interesting and comprehensive contemporary panorama.